Achieving Disagreement: From Indifference to Pluralism - Weigel, George (Journal of law and religion, 1990)
"Pluralism must not be confused with, and is in fact endangered by, philosophical and ethical indifference. Commitment to strong, clear philosophical and ethical ideas need not imply either intolerance or opposition to democratic pluralism. On the contrary, democratic pluralism requires an agreement to be locked in public argument over disagreements of consequence within the bonds of civility." - The Williamsburg CharterThe question of how we contend in the American public square on the many issues involved in the question of the First Amendment's religious clauses (or "clause," as some of us would insist) is inextricably bound up in the question of who constitutes the "we" involved in the contention. That is, how we contend must take account of who we are. Unless there is some clarity on this point, the debate over the nature of the civility to which we are called is doomed to be conducted at a perilous level of abstraction.As I survey the terrain from my own vantage point - that of a Roman Catholic theologian engaged in a host of issues and controversies at the intersection of moral norms and American public policy - the "we" involved here is a many splendored thing indeed. For our purposes, it seems to me that the "we" has at least four salient characteristics.